Analisis Proksimat Tepung Buah Pandan Laut (Pandanus tectorius) - Hernandes, Zimmi; Handayani, Lia; Mahgfira, Indria (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The fruit of the screw pine (Pandanus tectorius Park) is a biological resource that has not been optimally utilized, despite its potential as a nutrient-rich food source. This study aims to evaluate the chemical characteristics of screw pine fruit flour through proximate analysis. Fruit samples were collected from Gampong Ladong, Aceh Besar, then dried and ground into flour that passed through a 50-mesh sieve. The results of the proximate analysis showed that the flour contained 10.42% moisture, 7.22% ash, 1.98% fat, 2.79% protein, and 77.59% carbohydrates. These characteristics indicate that screw pine fruit flour has a feasible nutritional value and potential to be developed as an alternative food ingredient.